Negative electrode composite material of lithium ion battery, preparation method of negative electrode composite material, negative electrode pole piece and lithium ion battery
By covering the niobium tungsten oxide shell on the carbon material surface of the negative electrode material of the lithium-ion battery, the problem of low rate performance and safety risks of lithium-ion battery during high-rate charging and high-power charging is solved, and higher rate performance and better cycle stability and safety performance are achieved.
Patent Information
- Application Number
- CN202411753367.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
The existing lithium-ion battery anode materials have low rate performance and safety risks when charging at high rate and high power, such as the formation of lithium dendrites and short circuits in the battery.
The core-shell structure of carbon material coated with niobium tungsten oxide is used as the negative electrode composite material of lithium-ion battery. By forming a niobium tungsten oxide shell on the surface of the carbon material, the diffusion speed and charge transfer ability of lithium ions are improved.
It improves the rate performance and cycle stability of lithium-ion batteries, reduces the risk of lithium dendrites, enhances the safety performance of batteries, and can meet the needs of new energy vehicles and other electronic products for high-performance lithium-ion batteries.
Smart Images

Figure CN119560537A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and specifically relates to a lithium ion battery negative electrode composite material of niobium tungsten oxide coated carbon material, a preparation method thereof, a negative electrode sheet, and a lithium ion battery. Background Art
[0002] With the rapid development of modern society, people's demand and consumption of energy are also increasing, which has brought about increasingly prominent environmental problems such as solid waste pollution, water pollution and greenhouse gas emissions. Therefore, clean and renewable energy such as wind energy, solar energy, and tidal energy have been rapidly developed in countries around the world to reduce dependence on non-renewable traditional fossil energy such as coal and oil, and achieve energy conservation and emission reduction. The large-scale popularization of new energy vehicles based on lithium-ion batteries and the replacement of fuel vehicles, especially the advancement and promotion of energy storage technology, will be one of the effective ways to achieve this goal. This requires not only the improvement of energy replenishment measures such as the expansion of charging piles and the layout of battery replacement stations, but also the development of lithium-ion batteries with higher energy, higher rate and greater safety to meet the increasingly urgent demand for electrochemical energy in the future. This can be achieved from multiple aspects such as electrode liquid optimization, battery structure innovation, and battery management system upgrade, but the core key point is the innovation and optimization of positive and negative electrode materials of lithium-ion batteries.
[0003] Nowadays, the positive electrode materials of mainstream lithium-ion batteries are lithium iron phosphate or ternary lithium battery materials, the electrolyte is a liquid component composed of lithium salts, organic solvents and additives, and the negative electrode materials are carbon materials such as natural graphite, mesophase carbon microspheres, and artificial graphite. In particular, artificial graphite, with its theoretical capacity of up to 372mAh / g, excellent conductivity, stable cycle performance, low price, and abundant reserves, has gradually occupied a dominant position in the market. Today, its market share has stabilized at more than 80%. However, for the increasingly prominent energy replenishment needs such as the field of super-fast charging, its relatively low rate performance still cannot meet the actual needs of high-rate charging, that is, fast charging; at the same time, the high current density during high-power charging will cause lithium dendrites to form, causing short circuits in the battery, which has certain safety risks. This requires the development of higher-performance negative electrode materials or the compounding, modification and modification of carbon materials to meet their actual needs.
[0004] Coating carbon materials is the most effective method. For example, asphalt is used to coat pre-forged artificial graphite, and a soft carbon coating layer can be formed on the surface of artificial graphite after pre-oxidation treatment and carbonization. The electrochemical properties of artificial graphite can be significantly improved after coating, and it has been widely used in the field of high-end artificial graphite. However, this method does not significantly improve the rate performance of graphite. It is more about pre-forging and granulating to screen out artificial graphite with smaller particle size, and improving the rate performance by reducing the diffusion path of lithium ions. However, this method will cause a lot of manpower and material resources. Different material coatings can have different effects on the performance of artificial graphite negative electrodes, and the latest research on niobium tungsten tungsten oxide materials can have a variety of different similar chemical formulas according to the different molar ratios of niobium and tungsten, such as Nb 18 W 16 O 93 , Nb 16 W5W 55 , Nb 14 W3O 44 Etc., its theoretical capacity can reach 225mAh / g, and its unique open crystal structure gives the material a good lithium ion diffusion coefficient and cycle stability, so that the actual gram capacity of the material is very close to its theoretical capacity. According to reports, the gram capacity of niobium tungsten oxide can still reach 100mAh / g at 60C, and it still maintains a capacity retention rate of 95% after 1000 cycles at 20C. Therefore, when this material is used to coat carbon materials such as artificial graphite, the solid electrolyte layer (SEI) formed on the graphite surface will have good charge transfer ability and lithium ion diffusion rate, thereby achieving a more superior rate performance. In addition, niobium tungsten oxide material has Nb at a safe potential above 1V. 4+ / Nb 5+ and Nb 3+ / Nb 4+ This will help optimize the SEI film and avoid the formation of lithium dendrites, thereby giving the battery more superior long-cycle stability and safety performance. Summary of the invention
[0005] One of the purposes of the present invention is to provide a lithium ion battery negative electrode composite material to solve the problem of poor performance of lithium ion batteries in the prior art;
[0006] The second object of the present invention is to provide a method for preparing a lithium ion battery negative electrode composite material;
[0007] The third object of the present invention is to provide a negative electrode plate;
[0008] A fourth object of the present invention is to provide a lithium ion battery.
[0009] The purpose of the present invention can be achieved through the following technical solutions:
[0010] In a first aspect, a negative electrode composite material for a lithium ion battery, the negative electrode composite material having a core-shell structure, including a core and a shell layer;
[0011] The core is a carbon material, including but not limited to artificial graphite, natural graphite and other carbon materials;
[0012] The shell is niobium tungsten oxide, the chemical formula of which is Nb x W y O (5x+6y) / 2 , where x and y are integers or decimals that satisfy chemical equilibrium, generally in the range of 0≤x≤100; 0≤y≤100, including but not limited to N b18 W 16 O 93 , Nb 16 W5W 55 , Nb 14 W3O 44 .
[0013] Furthermore, the particle size of the carbon material is 1 to 20 μm, and the thickness of the niobium tungsten oxide is 1 to 200 nm;
[0014] Furthermore, the weight of the niobium tungsten oxide is 1% to 50% of the weight of the carbon material.
[0015] In a second aspect, a method for preparing a lithium ion battery negative electrode composite material comprises the following steps:
[0016] S1. Add the carbon material to the organic solvent, stir for 10 to 30 minutes, then add the niobium salt, and continue stirring for 10 to 30 minutes to obtain solution A;
[0017] S2. Add tungsten salt to an organic solvent and stir for 10 to 30 minutes to obtain a solution B, wherein the molar ratio of niobium and tungsten added satisfies the stoichiometric ratio of niobium tungsten oxide, that is, the molar percentage is x:y;
[0018] S3. Add solution B to solution A, stir for 30 to 60 minutes to obtain a mixed solution, add deionized water to the mixed solution, continue stirring to obtain a gel sol material, dry the solvent, and keep it at 60 to 90 ° C for 2 to 12 hours to obtain a mixed precursor;
[0019] Deionized water is added to the mixed solution. During the stirring reaction, after a certain period of time, the mixture gradually forms a "jelly-like" sol substance under the action of hydrolysis / alcoholysis, and the color of the solution also turns dark green. It is heated and dried to obtain the initial precursor of the niobium-tungsten mixture coated with carbon material.
[0020] S4. Place the mixed precursor under an inert atmosphere, heat it to 700-1200°C at a rate of 1-10°C / min, calcine it for 4-30 hours, and then naturally cool it to room temperature (25-30°C) to obtain a lithium-ion battery negative electrode composite material with a core-shell structure, wherein the core is a carbon material and the shell is niobium tungsten oxide, and the weight of the niobium tungsten oxide is 1% to 50% of the weight of the carbon material.
[0021] It should be noted that for a reaction chamber of about 8 L, the flow rate of the inert gas is 10 to 30 mL / min. A larger or smaller reaction chamber can be enlarged or reduced in the same proportion.
[0022] Furthermore, the organic solvent includes any one of ethanol, methanol, propanol, butanol, and acetone, or a mixture of several of them.
[0023] Furthermore, the niobium salt includes any one or a combination of niobium chloride, niobium acetate, niobium oxalate, niobium nitrate and niobium sulfate.
[0024] Furthermore, the tungsten salt includes any one or a combination of tungsten chloride, tungsten acetate, tungsten oxalate, tungsten nitrate, and tungsten sulfate.
[0025] Furthermore, the volume ratio of the organic solvent to deionized water in the mixed solution in S3 is (0.1-10):1.
[0026] In a third aspect, a negative electrode sheet includes a negative electrode current collector, on which the negative electrode composite material is coated.
[0027] In a fourth aspect, a lithium-ion battery comprises the negative electrode plate.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a lithium ion battery negative electrode composite material, the composite material has a core-shell structure, the core is a carbon material such as artificial graphite, natural graphite, etc., the shell is niobium tungsten oxide (chemical formula Nb x W y O (5x+6y) / 2 ) materials. A certain amount of raw materials such as carbon materials, tungsten salts, niobium salts, etc. are added to an organic solution, stirred and allowed to stand, and then reactants such as deionized water are added, and then the corresponding sol-gel products are generated under the action of hydrolysis / alcoholysis reactions. After drying, an initial coating layer of tungsten and niobium mixture can be formed on the surface of the carbon material; finally, after high-temperature treatment under an inert atmosphere, a carbon material composite material negative electrode coated with niobium tungsten oxide material is obtained. The composite material can be mixed with a certain amount of binder and conductive agent and coated on a current collector such as copper foil to form a negative electrode sheet, and then assembled into lithium-ion batteries, battery packs, and electronic devices such as 3C consumer electronics products and new energy vehicles.
[0030] 2. The coating of the outer layer of niobium tungsten oxide material can improve the charge transfer process of lithium ions on the surface of carbon materials and increase the diffusion rate of lithium ions, so that the carbon material has better rate performance; at the same time, the higher ion embedding potential and multiple redox point pairs of niobium tungsten oxide material can improve the performance of SEI film and prevent the formation of lithium dendrites, so that the battery has better cycle stability and safety performance, meeting the needs of new energy vehicles and various electronic products for high-performance lithium-ion batteries.
[0031] 3. The coating material on the surface of the carbon material is niobium tungsten oxide, which has Nb 18 W 16 O 93 , Nb 16 W5W 55 , Nb 14 W3O 44 It has a variety of different chemical structures and can be applied to different types of negative electrode material surfaces. The preparation method is flexible and varied. The theoretical capacity of the material itself can reach 225mAh / g, and it has a very high rate performance. It still maintains a capacity retention rate of more than 50% at a rate of 60C or even 100C. It can accelerate the charge transfer process of lithium ions on the electrode surface and the diffusion rate of lithium ions. The composite material formed has good rate performance. Secondly, niobium tungsten oxide material has Nb at a safe potential above 1V. 4+ / Nb 5 + and Nb 3+ / Nb 4+ This will help optimize the solid electrolyte (SEI) film and avoid the formation of lithium dendrites, thereby giving the battery more superior long-cycle stability and safety performance.
[0032] 4. The preparation method of the present invention is simple, scientific and efficient. Under the action of deionized water and organic solvents, the niobium-tungsten mixture undergoes hydrolysis / alcohololysis reaction to form a "jelly-like" sol-gel substance, which can form a uniform coating layer precursor on the surface of the carbon material. After further annealing treatment under an inert atmosphere, a carbon material composite material coated with niobium tungsten oxide can be obtained. The gel sol precursor has excellent adhesion. In addition to carbon materials, it also has a good coating effect on common lithium-ion battery negative electrode materials such as metal oxides, silicon, and lithium titanate, and has universal applicability. The entire preparation process does not involve extreme conditions such as high temperature and high pressure, and does not produce wastewater, waste gas and other pollutants that are difficult to treat. It is very easy to carry out industrial production and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention will be further described below in conjunction with the accompanying drawings.
[0034] Figure 1 It is a schematic structural diagram of a lithium ion battery negative electrode composite material of the present invention;
[0035] Figure 2 1 is a schematic diagram of a process for preparing a composite material for negative electrode of a lithium ion battery in Example 1 of the present invention;
[0036] Figure 3 is an X-ray diffraction pattern (XRD) of the mixed precursor sample after the mixed solution is dried in Example 1 of the present invention;
[0037] Figure 4 This is a scanning electron microscope image (SEM) of the negative electrode composite material obtained after high temperature annealing in Example 1 of the present invention;
[0038] Figure 5 is a cyclic voltammetry curve (CV) of the composite material obtained after high temperature annealing in Example 1 of the present invention;
[0039] Figure 6 The battery rate performance after the negative electrode composite materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are assembled into batteries;
[0040] Figure 7 The long-term cycle performance of the battery assembled from the negative electrode composite materials prepared in Examples 1 to 4 and Comparative Example 1 at a rate of 5C. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present disclosure. The embodiments of the present disclosure should not be interpreted as limiting the present disclosure.
[0042] the term:
[0043] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0044] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0045] In this document, it is necessary to understand that the orientations or positional relationships indicated by terms such as “upper”, “lower”, “top”, “bottom”, “inside” and “outside” are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0046] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0047] Unless otherwise specified, the terms used in this disclosure have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).
[0048] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. Such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0049] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0050] The present disclosure is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.
[0051] negative electrode:
[0052] In some embodiments of the present disclosure, the negative electrode includes a negative electrode sheet, and the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on the current collector, wherein the negative electrode active material layer includes the composite material involved in the present disclosure.
[0053] The material of the negative electrode current collector of the present disclosure is not particularly limited. In other embodiments of the present disclosure, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and a combination thereof.
[0054] In other embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil.
[0055] In some embodiments of the present disclosure, the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.
[0056] In some embodiments of the present disclosure, the negative electrode active material is the key to ensure that the negative electrode has good charge and discharge performance. The negative electrode active material of the present disclosure includes a negative electrode composite material, wherein the negative electrode composite material has a core-shell structure, including a core and a shell layer; Figure 1 As shown, the core is a carbon material, including but not limited to artificial graphite, natural graphite and other carbon materials with a particle size of 1 to 20 μm; the shell is niobium tungsten oxide, with a chemical formula of Nb x W y O (5x+6y) / 2 , where x and y are integers or decimals that satisfy chemical equilibrium, generally in the range of 0≤x≤100; 0≤y≤100, including but not limited to N b18 W 16 O 93 , Nb 16W5W 55 , Nb 14 W3O 44 , with a thickness of 1 to 200 nm; the weight of the niobium tungsten oxide is 1% to 50% of the weight of the carbon material.
[0057] In some embodiments of the present disclosure, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0058] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0059] In some embodiments of the present disclosure, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0060] positive electrode:
[0061] In some embodiments, the positive electrode includes a positive electrode sheet, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the current collector. The positive active material includes a compound that reversibly intercalates and deintercalates lithium ions. The positive active material may include a composite oxide containing lithium and at least one element selected from cobalt, manganese and nickel.
[0062] The specific types of positive electrode active materials are not subject to specific restrictions and can be selected according to needs. The positive electrode active material is selected from at least one of lithium cobalt oxide LiCoO2 (LCO), lithium nickel manganese cobalt ternary material (NCM), lithium iron phosphate, and lithium manganese oxide. They can be used alone or in any combination of two or more.
[0063] In other embodiments of the present disclosure, the positive electrode current collector may be selected from aluminum foil.
[0064] In some embodiments, the positive electrode active material may have a coating on the surface. The compound for the coating may be amorphous or crystalline, and the coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.
[0065] In some embodiments, the positive electrode active material layer further includes a binder, and optionally a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0066] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0067] In some embodiments, non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0068] Diaphragm:
[0069] In some embodiments of the present disclosure, the lithium ion battery and electrochemical device of the present disclosure are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.
[0070] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0071] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0072] Electrolyte:
[0073] The lithium-ion battery and electrochemical device involved in the present disclosure also include an electrolyte or a solid electrolyte.
[0074] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0075] In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB).
[0076] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0077] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0078] In some embodiments, the electrolyte may be a solid electrolyte such as lithium oxide garnet (Li7La3Zr2O 12 , LLZO), tin oxide (SnO2), bismuth oxide (Bi2O3) and other oxide electrolytes; lithium sulfide (Li2S), sodium sulfide (Na2S), thio-LISICON type Li 3.25 Ge 0.2 5P 0.7 S4, Argentum-type Li 6-x PS 5-x Cl 1+x (LPSC), Li7P3S in glass-ceramic state11 Sulfide electrolytes such as lithium polyacrylate (LiPAA), polyethylene glycol (PEO) and polymer electrolytes formed by their composites with lithium salts; one or more of the halide electrolytes such as LiYbF4, LiAlF4, Li3OC, LiBrO4, etc.
[0079] Lithium-ion battery:
[0080] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure includes the above-mentioned positive electrode plate, negative electrode plate, separator, electrolyte, solid electrolyte, etc., but is not limited thereto.
[0081] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure is made by stacking the above-mentioned positive and negative electrode sheets.
[0082] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure may include an outer packaging, and the outer packaging may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0083] In some embodiments, the present disclosure further provides a battery module. The battery module includes the above-mentioned lithium-ion battery. The battery module of the present disclosure uses the above-mentioned lithium-ion battery, and therefore has at least the same advantages as the lithium-ion battery. The number of lithium-ion batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0084] In some embodiments, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0085] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.
[0086] Example 1
[0087] See also Figure 2 , a method for preparing a lithium ion battery negative electrode composite material, comprising the following steps:
[0088] S1. Add 5 g of artificial graphite to 30 mL of ethanol, stir at room temperature for 30 min, then add 1.016 g of niobium chloride powder, and continue stirring for 30 min to obtain solution A;
[0089] S2. Add 0.466 g of tungsten chloride to ethanol and stir for 30 min to obtain solution B;
[0090] S3. Solution B was slowly added to solution A, stirred for 30 min to obtain a uniform mixed solution, 15 mL of deionized water was added to the mixed solution, and stirring was continued for 60 min, then the temperature was raised to 85 ° C and stirring was continued until the reaction solvent was dried, and the mixture was placed in an oven at 80 ° C for 12 h to obtain a mixed precursor;
[0091] The mixed precursor was weighed and the mass was 5.6930±0.0005 g. It was calculated that the mass of the outer precursor coating layer was 13.86±0.01% of the inner core artificial graphite.
[0092] The mixed precursor was subjected to XRD test, and the XRD spectrum obtained by the test was as follows: Figure 3 As shown, from Figure 3 It can be seen that the diffraction peaks are mainly those of carbon materials, proving that the outer coating of the precursor obtained is mainly amorphous phase hydrolysis products such as hydroxides and salts containing crystalline water, and has not yet formed good crystals.
[0093] S4. The mixed precursor was placed in a crucible, placed in a tubular furnace, nitrogen was introduced for 40 minutes at a gas flow rate of 30 mL / min, and the gas flow rate was adjusted to 20 mL / min, and the temperature was raised to 850°C at a rate of 10°C / min. After calcination for 6 hours, it was naturally cooled to room temperature, and the gas line was closed. The collected product was niobium tungsten oxide-coated carbon material with a mass of 5.3671±0.0005 g. It was calculated that the mass proportion of niobium tungsten oxide was 7.34±0.01% of graphite. Scanning electron microscopy (SEM) was used for characterization, and the morphology was as follows: Figure 4 As shown, it can be seen that there is an obvious coating layer on the surface of the negative electrode composite material.
[0094] Example 2
[0095] A method for preparing a lithium ion battery negative electrode composite material, which is different from Example 1 in that the amount of niobium chloride used is 0.508g, the amount of tungsten chloride used is 0.233g, the mass of the obtained mixed precursor is 5.2820±0.0005g, and it is calculated that the mass of the outer precursor coating layer is 5.46±0.01% of the inner core artificial graphite; the calcination temperature in S4 is 800°C, the calcination time is 4h, the mass of the calcined product is 5.1632±0.0005g, and it is calculated that the mass proportion of niobium tungsten oxide is 3.26±0.01% of graphite;
[0096] The remaining steps and parameters remain the same.
[0097] Example 3
[0098] A method for preparing a lithium ion battery negative electrode composite material, which is different from Example 1 in that the amount of niobium chloride used is 2.032g, the amount of tungsten chloride used is 0.932g, the mass of the obtained mixed precursor is 6.7260±0.0005g, and it is calculated that the mass of the outer precursor coating layer is 34.52±0.01% of the inner core artificial graphite; the calcination temperature in S4 is 950°C, the calcination time is 8h, the mass of the calcined product is 6.1328±0.0005g, and it is calculated that the mass proportion of niobium tungsten oxide is 22.66±0.01% of graphite;
[0099] The remaining steps and parameters remain the same.
[0100] Example 4
[0101] A method for preparing a lithium ion battery negative electrode composite material, which is different from Example 1 in that the amount of niobium chloride used is 3.049g, the amount of tungsten chloride used is 1.399g, the mass of the obtained mixed precursor is 7.5140±0.0005g, and it is calculated that the mass of the outer precursor coating layer is 50.28±0.01% of the inner core artificial graphite; the calcination temperature in S4 is 950°C, the calcination time is 12h, the mass of the calcined product is 6.6872±0.0005g, and it is calculated that the mass proportion of niobium tungsten oxide is 33.74±0.01% of graphite;
[0102] The remaining steps and parameters remain the same.
[0103] Comparative Example 1
[0104] The artificial graphite is dried at 100° C. for more than 24 hours to remove moisture absorbed on the surface, and then used as a negative electrode material without any further treatment.
[0105] Charge and discharge performance test:
[0106] The core-shell structure negative electrode composite material with niobium tungsten oxide coated carbon prepared in Examples 1 to 4 and the negative electrode material in Comparative Example 1 were mixed with conductive carbon black (SP), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 80:10:5:5 to form a slurry, and then evenly applied on copper foil, dried at 80°C for more than 12 hours, and then the dried copper foil was punched into a circular electrode sheet with a diameter of 1.2 cm. The electrode sheet loaded with the prepared sample was used as the positive electrode, and the circular metal lithium sheet with a diameter of 1.5 cm was used as the negative electrode. A mixed solution of 1 mol / L lithium hexafluorophosphate (LiPF6) in diethyl carbonate (DEC) and ethylene carbonate (EC) (volume ratio of 1:1) was used as the electrolyte. The diaphragm was a circular polypropylene film with a diameter of 19 mm. After assembling into a CR2032 button battery in an argon-filled glove box and placing it for 12 hours, the assembled battery performance was tested at a constant temperature of 25°C. The current density of charge and discharge at 1C rate is 350mA / g, and the voltage range is 0.005~3.0V.
[0107] The cyclic voltammetry curve of the sample in Example 1 is as follows: Figure 5 As shown, it can be seen that its redox peak position is still consistent with the reported artificial graphite sample, that is, after the artificial graphite is coated with niobium tungsten oxide, its main lithium deintercalation potential is still mainly based on the graphite body, and the outer coating layer only plays a role in improving the interface condition and accelerating the lithium ion deintercalation rate.
[0108] The rate performance and cycle capacity curves of different samples are shown in Figure 2. Figure 6 and Figure 7 As shown, graphite is the sample in comparative example 1; sample 1 is the product in example 2; sample 2 is the product in example 1; sample 3 is the product in example 3; sample 4 is the product in example 4. Figure 6 It can be seen from the rate performance test that the rate performance of the product of Example 1 is more excellent, significantly higher than that of other examples and comparative examples, especially after a 20C cycle, it can still return to the initial level. Figure 7 It was found from the cycle curves at 5C rate that after 1000 cycles, the final gram capacities of Examples 1 to 4 and Comparative Example 1 were 77.1, 152.9, 42.1, 62.4 and 41.8 mAh / g, respectively, of different samples, that is, the product of Example 1 still maintained a relatively high capacity after a long period of high-rate cycling, and its capacity gradually increased during the cycling process, indicating that it has a more excellent reaction interface, can curb the formation of lithium dendrites at high current density, and has better cycle stability and safety performance.
[0109] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0110] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A lithium ion battery negative electrode composite material, characterized in that: The negative electrode composite material has a core-shell structure, including a core and a shell layer; The core is made of carbon material. The shell is niobium tungsten oxide, the chemical formula of which is Nb x W y O (5x+6y) / 2 , where 0≤x≤100, 0≤y≤100.
2. A lithium ion battery negative electrode composite material according to claim 1, characterized in that: The particle size of the carbon material is 1 to 20 μm, and the thickness of the niobium tungsten oxide is 1 to 200 nm.
3. A lithium ion battery negative electrode composite material according to claim 1, characterized in that: The weight of the niobium tungsten oxide is 1% to 50% of the weight of the carbon material.
4. A method for preparing a lithium-ion battery negative electrode composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Add the carbon material to the organic solvent, stir for 10 to 30 minutes, then add the niobium salt, and continue stirring for 10 to 30 minutes to obtain solution A; S2. Add tungsten salt to organic solvent and stir for 10 to 30 minutes to obtain solution B; S3. Add solution B to solution A, stir for 30 to 60 minutes to obtain a mixed solution, add deionized water to the mixed solution, continue stirring to obtain a gel sol material, dry the solvent, and keep it at 60 to 90 ° C for 2 to 12 hours to obtain a mixed precursor; S4. Place the mixed precursor under an inert atmosphere, heat it to 700-1200°C at a rate of 1-10°C / min, calcine it for 4-30 hours, and then cool it naturally to room temperature to obtain a lithium-ion battery negative electrode composite material.
5. The method for preparing a lithium ion battery negative electrode composite material according to claim 4, characterized in that: The organic solvent includes any one of ethanol, methanol, propanol, butanol and acetone or a mixture of several of them.
6. The method for preparing a lithium ion battery negative electrode composite material according to claim 4, characterized in that: The niobium salt includes any one or a combination of niobium chloride, niobium acetate, niobium oxalate, niobium nitrate and niobium sulfate.
7. The method for preparing a lithium ion battery negative electrode composite material according to claim 4, characterized in that: The tungsten salt includes any one or a combination of tungsten chloride, tungsten acetate, tungsten oxalate, tungsten nitrate and tungsten sulfate.
8. The method for preparing a lithium ion battery negative electrode composite material according to claim 4, characterized in that: The volume ratio of the organic solvent to deionized water in the mixed solution in S3 is (0.1-10):
1.
9. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector, wherein the negative electrode current collector is coated with the negative electrode composite material according to any one of claims 1 to 3.
10. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Electrode composition
CN114730861A
Niobium pentoxide coated graphite composite negative electrode material and preparation method thereof
CN114864916A
Positive electrode material and positive plate and battery comprising positive electrode material
CN115440928A
Preparation method of multi-element positive electrode material with gradient composite structure
CN115924995A
Niobium-tungsten oxide with ordered alternate symbiotic crystal structure as well as preparation method and application thereof
CN117069150A